V.K. Krishna Menon remembered - Indian Society of International Law; Bal Hitkari Samiti (Kota, India) (New Delhi : Indian Society of International Law, 2005)
On the life and work of Vengalil Krishnan Krishna Menon, 1897-1974, Indian statesman; contributed lectures and speeches of Krishna Menon memorial lecture, a lecture series instituted by Bal Hitkari Samiti, Kota, India, to perpatuate his memory
Keywords: Krishna Menon, V. K. -- 1897-1974; Statesmen -- India -- Biography; India -- Politics and government -- 1919-1947; India -- Politics and government -- 1947-